1996
DOI: 10.1017/s0033291700035868
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of association between expanded CAG/CTG repeats and both schizophrenia and bipolar disorder

Abstract: SynopsisRecent studies have suggested that expanded CAG/CTG repeats contribute to the genetic aetiology of schizophrenia and bipolar disorder. However, the nature of this contribution is uncertain and difficult to predict from other known trinucleotide repeat diseases that display much simpler patterns of inheritance. We have sought to replicate and extend earlier findings using Repeat Expansion Detection in an enlarged sample of 152 patients with schizophrenia, 143 patients with bipolar disorder, and 160 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
57
2
4

Year Published

1997
1997
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(65 citation statements)
references
References 26 publications
2
57
2
4
Order By: Relevance
“…These studies have found a statistically significant shift towards longer CAG/CTG repeats in schizophrenic subjects compared to control individuals, with an overlap in the repeat length between patients and controls. [8][9][10] Nevertheless, in a previous study, we did not replicate these results in a population of sporadic patients. 11 Furthermore, we did not detect any CAG expansion in 21 multiplex families with anticipation, 11 and this negative result was also reported by Bassett et al 12 In order to identify candidate genes, investigators have screened for expansion in trinucleotide repeat-containing genes identified from human brain cDNA-libraries.…”
Section: Introductioncontrasting
confidence: 75%
“…These studies have found a statistically significant shift towards longer CAG/CTG repeats in schizophrenic subjects compared to control individuals, with an overlap in the repeat length between patients and controls. [8][9][10] Nevertheless, in a previous study, we did not replicate these results in a population of sporadic patients. 11 Furthermore, we did not detect any CAG expansion in 21 multiplex families with anticipation, 11 and this negative result was also reported by Bassett et al 12 In order to identify candidate genes, investigators have screened for expansion in trinucleotide repeat-containing genes identified from human brain cDNA-libraries.…”
Section: Introductioncontrasting
confidence: 75%
“…8,9 Further, the repeat expansion detection (RED) method has identified subjects with larger RED products of (CAG) n in bipolar disorder or schizophrenia compared to controls, with the implication that a locus with an enlarged (CAG) repeat is etiologically associated with the illness. [10][11][12][13][14] However, not all studies have found this. 15,16 We recently described a highly polymorphic (observed heterozygozity 84%) and unstable CAG repeat locus (CTG18.1) in the third intron of the SEF2-1 gene.…”
mentioning
confidence: 99%
“…1 This is interesting in view of several repeat expansion detection (RED) studies 2 that have reported an excess of large CAG repeats in psychotic probands. [3][4][5][6][7] Second, the hKCa3 gene is a functional candidate gene because studies of antipsychotic and psychotogenic compounds suggest that glutamatergic systems modulated by SKCa channels may be important in schizophrenia pathogenesis. 1 In the light of the above, we have tested the hypothesis of an association between schizophrenia and the hKCa3 CAG repeat polymorphism using a case control study design.…”
mentioning
confidence: 99%
“…Furthermore, while the hKCa3 gene is a reasonable candidate gene for schizophrenia as discussed above, the a priori case is not as strong as it might appear at first sight because the size of the repeat is too small to account for the RED data that have suggested an association between large CAG repeats and psychosis. [3][4][5][6][7] It should, however, also be noted that while the RED studies cannot be taken as supportive of the association between hKCa3 and psychosis, equally, they do not exclude such a possibility, nor does the size of the repeat in the hKCa3 gene alone exclude a pathogenic role since it is comparable to the size of repeat that causes SCA 6. 8 Our finding that a later age-at-onset is associated with a larger repeat length is contrary to expectations of the properties of disease-releated trinucleotide repeats.…”
mentioning
confidence: 99%